Surgical Revascularization of Lower Limb for Chronic Occlusive Arterial Diseases - Outcome of 35 Patients (University Heart Journal, 2011)
Background: Chronic lower limb ischemia is a dreadful disease and may present with intermittent claudication, rest pain and ischemic gangrene. Apart from life style modification and treating risk factors either angioplasty and stenting or surgical bypass are the mainstay of treatment. For infrainguinal bypasses reversed saphenous venous grafts are the conduits of choice because it is autologous , and have good patency rate. Endarterectomy is used in vessels of large caliber and may be added to bypass procedure.Objective: To study the outcome of surgical revascularization of the lower limb for chronic ischemia using reversed saphenous venous grafts.Methods: Thirty five cases of lower limb bypass surgery using reversed saphenous vein grafts were done for critical chronic lower limb ischemia from January, 2004 to December, 2008 and were analyzed for clinical success. The clinical success was defined as freedom from symptoms, avoidance of further revascularization, surgical or interventional or freedom from further amputation. The bypass procedures were femoro-popliteal, femoro-distal, femoral endarterectomy plus bypass, profundoplasty plus bypass. Data were collected, analyzed and results were recorded before discharge from the hospital, at 3 months, at 6 months and thereafter yearly follow up for up to 3 years.Results: The age range was 55 to 72 years (mean 62.34± 05.98 SD), 30 cases were male, 5 cases were female, all male patients were chronic smokers, 28 cases were diabetic, and 26 cases were hypertensive. Altogether 48 procedures were done, femoro-popliteal bypass were done in 30 cases, femoro-distal bypass were done in 7 cases (distal anastomotic sites were anterior tibial, posterior tibial or arteria dorsalis pedis), 9 cases had common femoral endarterectomy after which femoro-popliteal bypass were done, profundoplasty with femoro-popliteal bypass were done in 2 cases, 10 patient had to undergo either toe or transmetatarsal amputation. Three cases were subjected to below knee amputation at 2 to 3 years follow up due to recurrent ischemic rest pain with patchy gangrene. These were patients with femoral endarterectomy cases. The patency rate of grafts at 3 years was 65% for femoro-popliteal, 60% for femoro-distal, 57% for femoral endarterectomy with bypass and 58% for profundoplasty with bypass procedure.Conclusion: The graft patency rate and limb salvage rate for infrainguinal bypass procedure using reversed saphenous vein graft were quite satisfactory. Cessation of smoking, anti platelet and lipid lowering drug therapy, daily brisk walking for one hour and lifestyle modification improved the claudication distance and saved the limb and life in the study population. DOI: 10.3329/uhj.v6i2.7251University Heart Journal Vol. 6, No. 2, July 2010 pp.82-85